Ứng dụng Benford’s Law phát hiện dấu hiệu gian lận báo cáo tài chính của công ty niêm yết Việt Nam - Lâm Thị Trúc , Linh; Nguyễn Ngọc , Thọ; Nguyễn Hồng , Nga (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study applies Benford’s Law to detect the signal of financial statement fraud of Vietnamese listed companies. The data includes 600 observations from two items of revenue and profit after tax disclosed in the financial statements of 100 companies listed on the Vietnamese stock exchange from 2015 to 2020. The study has examined the distribution of the actual data in the first digit, the second digit, and the first-two digits. Three statistical tests including Z-statistics, Chi-square, and Mean Absolute Deviation (MAD) are used to assess the conformity of a data set to Benford’s Law. The result proves that the data do not comply with Benford’s Law in the first digit and the first-two digits leading to the financial statement signal fraud. This study recommends that auditors, fraud investigators could use Benford’s Law as a tool in detecting financial statement fraud.